2001
DOI: 10.1002/dvdy.1137
|View full text |Cite
|
Sign up to set email alerts
|

Multiple growth factors regulate coronary embryonic vasculogenesis

Abstract: Mechanisms regulating coronary vascularization are not well understood. To test hypotheses regarding the influence of key growth factors and their interactions, we studied vascular tube formation (vasculogenesis) in collagen gels onto which quail embryonic ventricles were placed and incubated in the presence of growth factors or inhibitors. Vasculogenesis in this model is dependent on tyrosine kinase receptors, since tube formation was totally blocked by genestein. Tube formation was attenuated when anti-bFGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 40 publications
10
58
0
1
Order By: Relevance
“…Studies have shown that VEGF mRNA is strongly expressed in the myocardium, and coronary capillary growth is dependent on VEGF during the prenatal and early postnatal period (30,31). Deficiency of VEGF 164 and VEGF 188 impairs myocardial angiogenesis and induces ischemic cardiomyopathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that VEGF mRNA is strongly expressed in the myocardium, and coronary capillary growth is dependent on VEGF during the prenatal and early postnatal period (30,31). Deficiency of VEGF 164 and VEGF 188 impairs myocardial angiogenesis and induces ischemic cardiomyopathy (5).…”
Section: Discussionmentioning
confidence: 99%
“…The epicardium and epicardially derived cells (EPDC) are pivotal to coronary vascular development (Pérez-Pomares et al, 1998;Pérez-Pomares et al, 2002;Dettman et al, 1998;Landerholm et al, 1999;Tomanek et al, 2001;Tomanek et al, 2008). However, there is not much known about the nature of the RA-dependent signals responsible for epicardial and EPDC proliferation, differentiation and involvement in myocardial growth (Kang and Sucov, 2005;Lavine et al, 2005;Merki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We have utilized quail heart explants in order to document the regulation of vasculogenesis and angiogenesis by specific growth factors and their interactions Tomanek, 1999, 2001;Tomanek et al, 2001Tomanek and Zheng, 2002;Holifield et al, 2004). Other studies have used chicken-quail chimeras to answer questions regarding the progenitor cells that contribute to the coronary circulation (Vrancken Peeters et al, 1997Peeters et al, , 1999Bergwerff et al, 1998;Gittenberger-de Groot et al, 1998, 2004Perez-Pomares et al, 1998;Manner, 1999;Eralp et al, 2005;Van Den Akker et al, 2005) or have examined specific aspects of coronary vessel (Bogers et al, 1989;Dettman et al, 1998;Perez-Pomares et al, 2002;Ando et al, 2004;Kattan et al, 2004;Pennisi and Mikawa, 2005).…”
mentioning
confidence: 99%